Larger than life : movie stars of the 1950s - Palmer, R. Barton, 1946-; Brown, William, 1977-; Hirsch, Foster; Krutnik, Frank, 1956-; Lawrence, Amy, 1957-; McLean, Adrienne L.; Pomerance, Murray, 1946-; Pugh, Tison; Sandler, Barry; Solomon, Matthew; White, Susan; Wojcik, Pamela Robertson, 1964- (Star decades: American culture/American cinema., 2010)
The constellation of Hollywood stars burned brightly in the 1950s, even as the industry fell on hard economic times. Major artists of the 1940s continued to exert a magical appeal but the younger generation of moviegoers was soon enthralled by an emerging cast, led by James Dean and Marlon Brando. They, among others, ushered in a provocative acting style, "the Method," bringing hard-edged, realistic performances to the screen. Larger Than Life offers a comprehensive view of the star system in 1950s Hollywood and also in-depth discussions of the decade's major stars.